Water quality assessment of Sg Serin, Sarawak - Srikaran, R.; Ling, Teck Yee; Nyantil, L.; Kho, C. P. (Universiti Malaysia Sarawak, 2013)
Due to its importance as a water supply and drinking sourcel the water quality of Sg Serin was assessed in this study from January to March 2009 based on temperature, pH, dissolved oxygen (~O), 5~day biochemical oxygen demand (BOD), organic phosphorus (Po), inorganic phosphorus (Pio) and trace metals (Ni, Zn, Pb). Results show that temperature ranged from 23.53 - 2S.36°C while pH ranged from 6.47 - 7.44 and that the sampling stations were all found to fall under Class II of the Interim National Water Quality Standards for Malaysia (INWQS) for pH. Measured DO ranged from 2.24 - 5.00 mg/L while BOD ranged from 1.86 - 7.99 mg/L where the lowest DO and highest BOD was measured in Sg Paml a tributary of Sg Serino This puts Sg Pam under Class IV for DO and Class III for BOD and its poor water quality can be attributed to discharge from animal farms. High BOD was also found in another two tributariesi Sg Bukah (7.22 mg/L) and Sg Penat (6.85 mg/L) whereby the high BOD can be associated with crop production and fish farming respectively. Sg Serin however falls under Class III for DO and Class II for BOD. Measured Po and Pro ranged from 0.45 - 21.11 mg/L and 0.04 - 4.64 mg/L respectively where the highest Po and Pro were both measured at Sg Pam and can be associated with oxidation pond effluent from animal farms. Ni concentration ranged from 0.011 - 0.020 ppm whereas Zn concentration ranged from 0.068 - 0.128 ppm and both trace metals were found to be at natural levels as specified under the INWQS. Pb however ranged from 0.018 - 0.114 ppm